Methicillin-Resistant Staphylococcus aureus: Docking-Based Virtual Screening and Molecular Dynamics Simulations to Identify Potential Penicillin-Binding Protein 2a Inhibitors from Natural Flavonoids - Masumi, Motahareh; Noormohammadi, Fatemeh; Kianisaba, Fatemeh; Nouri, Fatemeh; Taheri, Mohammad; Taherkhani, Amir (International Journal of Microbiology, 2022)
Staphylococcus aureus (S. aureus) is responsible for several disorders including skin and soft tissue infections, bacteremia, pulmonary infections, septic arthritis, osteomyelitis, meningitis, gastroenteritis, toxic-shock syndrome, and urinary tract infections. Methicillin-resistant S. aureus (MRSA) contains penicillin-binding protein 2a (SauPBP2a) responsible for catalyzing the peptidoglycan production within the bacterial cell wall. The binding affinity of SauPBP2a to beta-lactam antibiotics is low, and thus, it is necessary to discover new effective SauPBP2a inhibitors to combat mortality and morbidity in patients affected by MRSA. The binding affinity of 46 natural flavonoids to the SauPBP2a active site was examined via molecular docking analysis. The stability of docked poses associated with the top-ranked flavonoids was tested by performing molecular dynamics (MD) in 10 nanoseconds (ns) computer simulations. Kaempferol 3-rutinoside-7-sophoroside and rutin demonstrated a considerable binding affinity to the SauPBP2a active site (ΔGbinding < −11 kcal/mol). Their docked poses were found to be stable for 10 ns MD simulations. Kaempferol 3-rutinoside-7-sophoroside and rutin also exhibited salient binding affinity to the enzyme’s allosteric site. This study suggests that kaempferol 3-rutinoside-7-sophoroside and rutin may be considered as drug candidates for therapeutic aims in several human infections associated with MRSA. Nevertheless, in vitro and in vivo confirmations are warranted.